2001
DOI: 10.1073/pnas.141136098
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic consumption of nitric oxide by 12/15- lipoxygenase: Inhibition of monocyte soluble guanylate cyclase activation

Abstract: 12͞15-Lipoxygenase (LOX) activity is elevated in vascular diseasesarachidonate ͉ linoleate ͉ hypertension ͉ atherosclerosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 62 publications
(62 reference statements)
1
42
0
Order By: Relevance
“…We have also recently shown that these 12-LO-overexpressing cells (m12-LO cells) have a greater rate of nitric oxide consumption than the control cells (pcDNA cells). This suggests that LOs may contribute to vascular dysfunction not only by the bioactivity of their lipid products, but also by serving as a catalytic sink for nitric oxide in the vasculature (40). These studies provide additional support for the important role of vascular and mononuclear 12-LO in vascular disorders.…”
Section: Discussionmentioning
confidence: 67%
“…We have also recently shown that these 12-LO-overexpressing cells (m12-LO cells) have a greater rate of nitric oxide consumption than the control cells (pcDNA cells). This suggests that LOs may contribute to vascular dysfunction not only by the bioactivity of their lipid products, but also by serving as a catalytic sink for nitric oxide in the vasculature (40). These studies provide additional support for the important role of vascular and mononuclear 12-LO in vascular disorders.…”
Section: Discussionmentioning
confidence: 67%
“…Overall this would suggest different pathways for NO consumption. It has been shown for example that 15-lipoxygenase, prostaglandin-H synthase, and myeloperoxidase all consume NO to yield nitrite, and it is possible that these pathways may prevail under specific conditions (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, NO inactivation in non-striated tissues is poorly understood, and examination of NO consumption in various cells suggests mechanisms that differ in NO saturation, oxygen and cyanide sensitivity, and product formation (5)(6)(7)(8). Specific pathways include increased partition of NO in cell membranes (7) and consumption of NO by cytochrome c oxidase (9 -11), NADPH oxidase (12), 15-lipoxygenase (13), prostaglandin-H synthase (14), and myeloperoxidase (15).…”
Section: Nitric Oxide (No)mentioning
confidence: 99%
“…44 Our present observations of reduced growth and matrix responses in VSMC from LOKO mice suggest that these could be additional mechanisms for the atheroprotective role conferred by ablation of 12/15-LO. Since LO activation can lead to the consumption of nitric oxide, 45 this could be another key route by which vascular LO mediates the pathogenesis of atherosclerosis and hypertension. Patricia et al 46 showed that 12(S)-HETE treatment of endothelial cells could lead to increased monocyte binding and that the 12/15-LO ribozyme blocked high glucoseinduced binding of monocytes to endothelial cells.…”
Section: Discussionmentioning
confidence: 99%